UPAYA MENINGKATKAN KEMAMPUAN OKUPASI ANAK TUNAGRAHITA SEDANG MELALUI PELAKSANAAN PROGRAM TERPADU BHAKTI LUHUR - Sri Wahyuni; Supi Supi (Jurnal Pelayanan Pastoral, 2021)
Children with moderate mental retardation are a category of children who need assistance in learning everything including in the field of household work occupations. The Bhakti Luhur Integrated Program (PTBL) is a flagship program used by the Bhakti Luhur Foundation that is involved in handling people with disabilities, one of which is mentally retarded children. One of the fields in the Integrated Bhakti Luhur Program (PTBL) is the occupational field with the sub-sector of household work. This study aims to assess whether household work occupational training is effective in improving the ability of children with moderate mental retardation. This study uses a quantitative descriptive research design, with the subject of 4 children with moderate mental retardation. The data collection method used is full participant observation. Meanwhile, data analysis was carried out by processing the final test minus the initial test and then presenting it. The results showed that: for the PU subject from the four exercise items, the results were 50.8%, for the PA subject from the four exercise items the results were 56%, for the AG subject from the four exercise items the results were 65%, for the MZ subject from the four exercise items the results were obtained. 82.5%.